2018
DOI: 10.1007/s10787-018-0487-8
|View full text |Cite
|
Sign up to set email alerts
|

Propolis modulates NOS2/arginase-1 pathway in tropomyosin-induced experimental autoimmune uveitis

Abstract: In this study, we evaluated the preventive and curative effects of ethanolic extract of Propolis (EEP) during α-Tropomyosin-induced uveitis in an experimental model using Wistar rats, through the regulation of inducible nitric oxide synthase (NOS2) and arginase-1. In this context, rats received daily injection of EEP (100 mg/kg) for 5 days prior to immunization or for 9 days commencing 5 days post immunization with α-Tropomyosin extract, then were sacrificed at day 14. Histological examination, NOS2, arginase-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 45 publications
3
7
0
Order By: Relevance
“…As previously reported by our team, during EAU activity, a signi cant proportion of damages in ocular structures was observed and attributed mainly to nitric oxide (Djeraba et al 2010;Arroul-Lammali et al 2012;Touri et al 2019). In addition, TNF-α, has been shown to be an important cytokine involved in alteration of ocular tissue (Dick et al 2004).…”
Section: Discussionsupporting
confidence: 79%
“…As previously reported by our team, during EAU activity, a signi cant proportion of damages in ocular structures was observed and attributed mainly to nitric oxide (Djeraba et al 2010;Arroul-Lammali et al 2012;Touri et al 2019). In addition, TNF-α, has been shown to be an important cytokine involved in alteration of ocular tissue (Dick et al 2004).…”
Section: Discussionsupporting
confidence: 79%
“…It is clear from the viability data and the enhancement of energy metabolites such as ATP and creatine phosphate that propolis if anything increases the viability of the cultured macrophages. The cytokine assays largely support the reports [ 3 , 4 , 5 , 6 ] that propolis is anti-inflammatory and the metabolomics data almost perfectly support the idea that propolis treatment is pushing the macrophages towards an M2-like character. The conversion of arginine to citrulline with the formation of NO is inhibited, and levels of GSH and GSSH are increased, pointing towards the promotion of activity against ROS generation; a number of intermediates required for GSH biosynthesis are elevated by propolis treatment.…”
Section: Discussionsupporting
confidence: 76%
“…In the UK, Northern Europe, and North America, propolis is collected from poplar trees and their relatives; in Southern Europe and North Africa, much of it comes from Cypress trees; and in tropical regions such as Brazil and West Africa, propolis is usually collected from many different plant sources [ 1 , 2 ]. There are numerous literature reports on the immunomodulatory effects of propolis [ 3 , 4 , 5 , 6 , 7 , 8 ]. In a recent paper, we studied several types of propolis for their effects on the metabolic response of THP-1 cells to treatment with lipopolysaccharide (LPS), and for one sample from Cameroon, which inhibited cytokine release, we studied the metabolomics of the immune response and found a clear effect of the propolis in inhibiting purine nucleotide phosphorylase [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Other authors have found similar results as [255] for propolis from Algeria, which showed immunomodulatory and anti-inflammatory effect in animals with uveitis induced by α-tropomyosin. [293] Mouse et al [120] did a screening of the antitumor potential of Moroccan propolis extracts, from Beni Mellal region, in P815 tumor-bearing mice and have found that the treatment with propolis have the capacity to reduce the tumor volume as compared with the control. [120] Mountassir et al [294] have investigated samples from the same region regarding its possible antinociceptive activity and have conclude that propolis activated both central and peripheral mechanisms to elicit the analgesic effect in tested animals.…”
Section: Application In Medicine Pharmacy and Bio-allied Sciencementioning
confidence: 99%